PENGARUH MOTIVASI SPRITUAL AGAMIS DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA PEGAWAI - Yusuf Ande; Nurwati Nurwati; La Ode Bahana Adam (Pascasarjana Universitas Halu Oleo, 2017)
This study aimed to examine the effect of religious spiritual motivation and democratic leadership on performance of staff at the Office of Agriculture of Muna regency. The type of the study was quantitative research. Samples of the study were 76 staff of the Office of Agriculture of Muna regency. Data were collected from the respondents, and were analyze using the multiple linear regression analysis on the SPSS 22. Results of the study showed thatreligious spiritual motivation had a positively significant effect on performance of staff at the Office of Agriculture of Muna regency, with the coefficient of correlation 0.439 (p < 0.08), and democratic leadership on performance of staff at the Office of Agriculture of Muna regency, with the coefficient of correlation 0.262 (p < 0.08). The significance of the study was on the development of science, especially in the area of organizational behaviors of civil servants. Keywords: religious spiritual motivation, democratic leadership, performance of staff